(untitled) (Palimpsesto, 2018)
On the margins of Official History systematized and filtered by a specific ideological perspective, runs the flow of another history composed of events not yet ordered, real or fictitious voices, testimonial images that through the visual, evince an inscription of the present which also corresponds to the absent. In this autobiographical text, this other history is inscribed in individual experience, in the sphere of a Subjectivity that reacts both intellectually and emotionally to these scattered fragments of a disaster inserted in memory, everyday life, art and literature.